2020
DOI: 10.3390/foods9101435
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Cold Plasma Technology in Ensuring the Safety of Foods and Agricultural Produce: A Review

Abstract: Cold plasma (CP) is generated when an electrical energy source is applied to a gas, resulting in the production of several reactive species such as ultraviolet photons, charged particles, radicals and other reactive nitrogen, oxygen, and hydrogen species. CP is a novel, non-thermal technology that has shown great potential for food decontamination and has also generated a lot of interest recently for a wide variety of food processing applications. This review discusses the potential use of CP in mainstream foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 67 publications
0
56
0
Order By: Relevance
“…In biomedical field, plasma applications extend from sterilization, wound healing to cancer fighting [Larroussi 2020]. In agriculture, plasma is used to treat seeds, improve crop growth, and assure food safety [Varilla et al 2020]. In environmental applications, plasma is used in air purification control [Giardina et al 2020].…”
Section: Effect Of Water Parameters On Decolourization Efficiency Ofmentioning
confidence: 99%
“…In biomedical field, plasma applications extend from sterilization, wound healing to cancer fighting [Larroussi 2020]. In agriculture, plasma is used to treat seeds, improve crop growth, and assure food safety [Varilla et al 2020]. In environmental applications, plasma is used in air purification control [Giardina et al 2020].…”
Section: Effect Of Water Parameters On Decolourization Efficiency Ofmentioning
confidence: 99%
“…Some recent studies have focused on the potential application of cold plasma as non-thermal pasteurization or sterilization methods for different food products, such as meat, cheese, cereals or vegetables [ 174 , 175 ]. Varila, Marcone and Annor [ 174 ] described the efficiency of cold plasma technology in extending the shelf-life of meat products, due to its ability to inactivate a wide spectrum of microorganisms, including biofilms, fungi, spores and some viruses.…”
Section: Alternative Technologiesmentioning
confidence: 99%
“…Some recent studies have focused on the potential application of cold plasma as non-thermal pasteurization or sterilization methods for different food products, such as meat, cheese, cereals or vegetables [ 174 , 175 ]. Varila, Marcone and Annor [ 174 ] described the efficiency of cold plasma technology in extending the shelf-life of meat products, due to its ability to inactivate a wide spectrum of microorganisms, including biofilms, fungi, spores and some viruses. Multiple studies have demonstrated that cold plasma treatment of meat and meat products was efficient for the inactivation of some pathogens like Staphylococcus aureus (Beef jerky) [ 176 ], Salmonella enterica and Campylobacter jejuni (Skinless chicken breast and chicken tight) [ 177 ], Escherichia coli and Listeria monocytogenes (Raw pork loin) [ 178 ] and Salmonella typhimurium (Bacon) [ 179 ].…”
Section: Alternative Technologiesmentioning
confidence: 99%
“…The application of non-thermal plasma (NTP) generated at atmospheric pressure is a promising physical approach ( 20 , 21 ). Plasmas are ionized gases containing neutral- and free charged particles such as ions and electrons ( 22 , 23 ). Novel intervention technologies for fresh foods demand minimal processing at low or mild heat temperatures to maintain fresh characteristics, as well as compatibility with high throughput continuous processing, which can be achieved through non-thermal plasma at atmospheric pressure in gas or functionalized liquid mode of delivery ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Plasmas are ionized gases containing neutral- and free charged particles such as ions and electrons ( 22 , 23 ). Novel intervention technologies for fresh foods demand minimal processing at low or mild heat temperatures to maintain fresh characteristics, as well as compatibility with high throughput continuous processing, which can be achieved through non-thermal plasma at atmospheric pressure in gas or functionalized liquid mode of delivery ( 22 ). PTW can be used as the transport medium of reactive species and antimicrobial components for food, water, and surface sanitation ( 24 ).…”
Section: Introductionmentioning
confidence: 99%